Biofunctional Polyvinyl Alcohol/Xanthan Gum/Gelatin Hydrogel Dressings Loaded with Curcumin: Antibacterial Properties and Cell Viability - Garcia-Mena, V; Ortiz-Nunez, J; Cament-Riveros, A (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
This study explores the development of biocompatible hydrogel dressings incorporating curcumin as an alternative antibacterial agent. In this context, hydrogels were prepared using polyvinyl alcohol, xanthan gum, gelatin, and curcumin as a therapeutic component. FTIR spectroscopy confirmed the successful incorporation of curcumin into the hydrogel matrix, while release profiles demonstrated sustained release. Mechanical testing indicated that xanthan gum reduced elongation and strength in hydrogels, while the combination of xanthan gum and gelatin increased stiffness without loss of elasticity. Curcumin had no major effect on the tensile and rheological properties, preserving the structural integrity of the hydrogels. The hydrogels demonstrated antibacterial activity against Pseudomonas aeruginosa and Staphylococcus aureus ATCC strains, as well as multidrug methicillin-resistant Staphylococcus aureus (MRSA) clinical isolates. Biocompatibility was confirmed through viability assays with immortalized human keratinocytes (HaCaT) and adult human dermal fibroblasts (HDFa), showing no acute cytotoxic effects after 48 h of exposure. Their effective action against clinically relevant bacteria and high cytocompatibility position these hydrogels as promising candidates for infection management and antibiotic resistance mitigation in wound care applications.
Keywords: hydrogel; curcumin; antibacterial activity; cytocompatibility; MRSA